Maintenance With Hypomethylating Agents After Allogeneic Stem Cell Transplantation in Acute Myeloid Leukemia and Myelodysplastic Syndrome: A Systematic Review and Meta-Analysis - Kungwankiattichai, Smith; Ponvilawan, Ben; Roy, Claudie; Tunsing, Pattaraporn; Kuchenbauer, Florian; Owattanapanich, Weerapat (Frontiers in Medicine, 2022)
Introduction: Hypomethylating agents (HMAs) seem to have a range of properties favorable to post-allogeneic hematopoietic stem cell transplantation (allo-SCT) maintenance in acute myeloid leukemia (AML) patients. Materials and Methods: The investigators searched eligible studies which compared HMA maintenance to observation following allo-SCT for AML or myelodysplastic syndrome. Results: The meta-analysis eligibility criteria were fulfilled by 11 studies. The overall survival and relapse-free survival of the HMA maintenance group were superior to the observation group, with a pooled odds ratio (OR) of 2.52 and 2.64, respectively. Moreover, the cumulative incidence of relapse was significantly lower in those who received HMAs. The HMA group also had lower non-relapse mortality compared with the observation group. Overall, the incidences of grades II–IV acute graft-versus-host disease (GVHD) and chronic GVHD did not differ in both groups. However, when looking specifically at those receiving decitabine maintenance, the rate of chronic GVHD seemed to be lower compared with observation alone. Conclusions: The current systematic review and meta-analysis illustrated that AML and MDS patients receiving HMA maintenance after allo-SCT had better outcomes in regards to OS, RFS, NRM, CIR as well as a reduced incidence of chronic GVHD.